Complete Genome Sequence of Middle East Respiratory Syndrome Coronavirus KOR/KNIH/002_05_2015, Isolated in South Korea - Kim, You-Jin (Genome Announc, 2015)
The full genome sequence of a Middle East respiratory syndrome coronavirus (MERS-CoV) was identified from cultured and isolated in Vero cells. The viral genome sequence has high similarity to 53 human MERS-CoVs, ranging from 99.5% to 99.8% at the nucleotide level.